2022
DOI: 10.1097/mnh.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor prolyl hydroxylase enzyme inhibitors: ready for primetime?

Abstract: Purpose of reviewHypoxia-inducible factor (HIF) prolyl hydroxylase inhibitors have recently been developed as a new treatment for anemia associated with chronic kidney disease (CKD). Several of these have been approved in Europe (roxadustat), China, and Japan, but none approved in the United States to date, although daprodustat has been submitted as a new drug application to the Food and Drug Administration. The aim of this review is to critically appraise the available data, particularly the most recent publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…As a hypoxia-inducible factor prolyl hydroxylase inhibitor, roxadustat stabilizes hypoxia-inducible factors and stimulates the expression of the erythropoietin gene. It promotes increases in the concentrations of erythropoietin in certain organs, including the kidneys and liver, which is beneficial for maintaining Hb levels (26). In our study, the convenience of orally administered roxadustat resulted in high treatment compliance and led to more effective treatment than rhEPO for improving anemia.…”
Section: Discussionmentioning
confidence: 62%
“…As a hypoxia-inducible factor prolyl hydroxylase inhibitor, roxadustat stabilizes hypoxia-inducible factors and stimulates the expression of the erythropoietin gene. It promotes increases in the concentrations of erythropoietin in certain organs, including the kidneys and liver, which is beneficial for maintaining Hb levels (26). In our study, the convenience of orally administered roxadustat resulted in high treatment compliance and led to more effective treatment than rhEPO for improving anemia.…”
Section: Discussionmentioning
confidence: 62%
“…However, because the pathogenesis of DM is complex and the degree of hypoxia varies in different tissues, research on the treatment of diabetes and its complications by improving tissue hypoxia is still under further investigation. Roxadustat has been approved for the treatment of CKD anemia in Europe, China, and Japan, while other HIF-PH inhibitors have been approved in China and Japan alone (Macdougall, 2022). Comparing with other PHD inhibitors, roxadustat is generally well-tolerated and has been used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological manipulation of PHD-HIF axis has been quested for treating disorders related to local and systemic hypoxia. PHD inhibitors were developed for the treatment of chronic kidney disease (CKD)-related anemia ( Welden et al, 2017 ; Semenza, 2019 ; Wish et al, 2021 ; Macdougall, 2022 ). At least six PHD inhibitors roxadustat (FG-4592), daprodustat (GSK1278863), vadadustat (AKB-6548), molidustat (BAY 85-3934), enarodustat (JTZ-951) and desidustat have been developed and the phase 3 clinical trials showed that their effects were non-inferior to current EPO-stimulating agents ( Sugahara et al, 2022 ).…”
Section: Phd Inhibitors For Ibd Treatmentmentioning
confidence: 99%